Diagnostic value of carcinoembryonic antigen and carcinoma antigen 19-9 for colorectal carcinoma - Zhang, Shi-Yan (Int J Clin Exp Pathol, 2015)
Objective: The purpose of this study was to evaluate the diagnostic efficiency of colorectal carcinoma (CRC) with the tumor markers Carcinoembryonic Antigen (CEA) and Carbohydrate Antigen 19-9 (CA 19-9), in addition to investigating whether CA 19-9 can be used to screen the disease process in patients with CRC who had no elevation of CEA levels. Methods: Serum levels of CEA and CA 19-9 were measured in: 138 patients with CRC; 111 patients with benign colorectal diseases. The diagnostic value was performed using the logistic regression equation and receiver operating characteristic curves (ROC). Results: The serum levels of CEA and CA 19-9 in the patients with CRC were significantly higher than those in the patients with benign colorectal diseases (P < 0.001). Receiver operating characteristic curves (ROC) in the patients with CRC versus those with benign colorectal disease yielded the optimal cut-off value of 3.36 ng/ml for CEA and 23.9 U/ml for CA 19-9, respectively. The area under ROC curve (AUC) was 0.789 for CEA, 0.690 for CA 19-9 and 0.900 for the combination of the two tumor markers. The combination resulted in a higher Youden index and a sensitivity of 85.3%. Conclusion: The combined detection of serum CEA and CA 19-9 could play a pivotal role in the diagnosis of CRC, and could drastically improve the sensitivity for the diagnosis of CRC. CA 19-9 might be a tumor biomarker in addition to CEA for CRC.